Outcomes of haploidentical peripheral stem cell transplantation with combination of post-transplant cyclophosphamide (PTCy) and anti-thymocyte globulin (ATG) compared to unrelated donor transplantation in acute myeloid leukemia: A retrospective 10-year experience. (September 2022) - Barkhordar, Maryam; Kasaeian, Amir; Janbabai, Ghasem; Mousavi, Seied Asadollah; Fumani, Hossein Kamranzadeh; Tavakoli, Sahar; Bahri, Tanaz; Ghavamzadeh, Ardeshir; Vaezi, Mohammad
Abstract: In the evolution of haploidentical hematopoietic stem cell transplantation (haplo-HSCT), In vivo T-cell modulation with concomitant use of anti-thymocyte globulin (ATG) and high-dose post-transplant cyclophosphamide (PTCy) provides a novel promising method on transplant outcomes; however, the long-term effects of this therapy are mostly unknown. We retrospectively compared the long-term outcomes of adult acute myeloid leukemia (AML) patients undergoing a haplo-HSCT (n = 92) with a new modified combination of ATG and PTCy in the context of peripheral blood stem cell (PBSC) and myeloablative conditioning (MAC) with an otherwise similar group of AML patients who received an unrelated donor (URD) HSCT (n = 57) with ATG protocol from February 2010 to December 2020 at our single-center (HORCSCT). Median follow-up was 3.73 and 4.28 years for haploidentical and URD-HSCT, respectively. In haplo-HSCT, the cumulative incidence of grades II-IV and III-IV acute graft versus host disease (aGvHD) and extensive chronic GvHD (cGvHD) was much lower than in URD (27% versus 56% for grades II-IV, 8.7% versus 24.5% for grades III-IV, and 15.4% versus 34.7% for extensive cGvHD, respectively). Five-year overall survival (OS) was 54.03% for haplo and 54.48% for URD (p = 0.927); GvHD-free relapse-free survival (GRFS) was 44.1% and 29.86% (p = 0.149); relapse incidence was 15.79% and 26.95% (p = 0.72); and non-relapse mortality (NRM) was 29.48% and 26.32% (p = 0.73), respectively. Using multivariable analyses, when compared to Haplo, URD was a significant predictor of relapse (HR=1.80, p = 0.039); however, no difference in OS, GRFS, and NRM was noted between haplo and URD. Therefore, given the favorable results with haplo-HSCT and considering donor availability promptly with low cost, it conservatively suggested that haplo-HSCT with the introduced protocol could be viewed as the first alternative for patients with AML in the absence of matched sibling donors. Highlights: Compared to URD, haplo-PBCT with ATG/PTCy resulted in a comparable OS, GRFS. Compared to URD, haplo-PBCT with ATG/PTCy resulted in a comparable NRM. Compared to URD, haplo-PBCT with ATG/PTCy resulted in a lower relapse incidence. Compared to URD, aGvHD, and extensive cGvHD incidence in haplo-PBCT were much lower. Compared to URD, haplo-HSCT have superior OS and GRFS in the first remission of AML.